Operation analysis in the optimization of the citrus waxing process - Arenas Arrieta, Inelvy de los Ángeles (2022)
Mexico is one of the leading citrus producers worldwide. This work presents an analysis for improving the citrus waxing process in a company dedicated to this activity, located in the town of Álamo, Temapache, in the northern part of the state of Veracruz, Mexico. This study used the ten approaches to operations analysis to find areas of opportunity where the company could improve; the implementation of lean manufacturing tools such as 5s, Kaizen, and autonomous maintenance was suggested to optimize the waxing process. As a result of this analysis, an improvement proposal was developed regarding simplifying operating procedures, improving the handling of materials, and optimal use of equipment, allowing the company to be more efficient and productive.